HLA Haplotype Mismatch Transplants and Posttransplant Cyclophosphamide - Andrea Bacigalupo; Simona Sica (Advances in Hematology)
The use of high dose posttransplant cyclophosphamide (PT-CY) introduced by the Baltimore group approximately 10 years ago has been rapidly adopted worldwide and is becoming a standard for patients undergoing unmanipulated haploidentical (HAPLO) transplants. PT-CY has been used following nonmyeloablative as well as myeloablative conditioning regimens, for bone marrow or peripheral blood grafts, for patients with malignant and nonmalignant disorders. Retrospective comparisons of HAPLO grafts with conventional sibling and unrelated donor grafts have been published and suggest comparable outcome. The current questions to be answered include the use of PT-CY for sibling and unrelated donors transplant, possibly in the context of prospective randomized trial.